Antimeningococcal Vaccination Coverage Among Healthcare Workers in an Italian University Hospital - Gattini, Vittorio; Napoletano, Marco; Bonotti, Alessandra; Mignani, Aldo; Cosentino, Francesca; Guglielmi, Giovanni; Fallahi, Poupak; Cristaudo, Alfonso; Foddis, Rudy (Frontiers in Public Health, 2021)
Introduction: Following an outbreak of meningococcal epidemic in 2015 and 2016 in Tuscany, we registered a higher demand for antimeningococcal vaccination (anti-Men ACWY) by Healthcare Workers of the University Hospital of Pisa [Azienda Ospedaliero Universitaria Pisana (AOUP)]. The purpose of this work is to analyze and discuss data on vaccination coverage resulting from this vaccination campaign. Materials and Methods: We conducted a monocentric study about anti-Men vaccination in the healthcare workers of the AOUP following the outbreak of meningococcal meningitis that occurred mainly in the population of the Tuscan provinces of Pisa, Pistoia, Prato, and Florence. The variables under examination were age, sex, educational qualification, and job profile. Department healthcare workers were vaccinated with two types of conjugated tetravalent vaccines for the A, C, Y, and W135 strains. Data were analyzed using the SPSS software. Results: The total population of the workers in AOUP was 7,188 subjects; the population considered in the study was 5,889. Between 2015 and 2017, a total of 2,423 subjects (41.1%) underwent anti-Men vaccination. Women, older HCWs, those with a lower educational qualification, doctors, and the HCWs of the maternal and child department, and imaging department recorded a statistically significant better vaccine compliance. Discussion: The AOUP, implementing the program of the Tuscany Region of vaccination against Neisseria meningitidis, has contributed to reduce the incidence of invasive meningococcal disease. Some critical issues remain in the compliance of some sections of the population, despite the high level of adherence recorded in this case, probably also due to the great media coverage of the event.